Research in sustainability: highly needed and feasible! Research in sustainability: highly needed and feasible! - Sperna Weiland, Nicolaas (Journal of the Portuguese Society of Anesthesiology, 2025)
We are currently living in a new geological era: the Anthropocene, where humanity has become the dominant force in the shaping of the Earth’s environment.(1) The evolving challenges of environmental pollution, climate change, biodiversity loss and the associated health consequences demand that healthcare, itself a polluting sector responsible for 5-10% of global greenhouse gas emissions, develops sustainable solutions.(2,3) The European Society for Anaesthesiology and Intensive Care (ESAIC) has put forward the Glasgow Declaration, defining priority areas to mitigate the carbon footprint of anaesthesia.(4) Delivering these goals requires a profound transformation of our profession and the healthcare system in general. To help us navigate this challenge, we need scientific research to guide us. In the context of 'planetary health', it is crucial to create effective strategies for climate mitigation and adaptation, facilitate their implementation, build relevant datasets to inform policy, and develop innovative approaches to planetary health research.